Lesson learned from vocational training center as a school-to-work transition program in Indonesia - Hamid, Mustofa Abi; Siswantoyo, Siswantoyo; Gunadi, Gunadi; Setiawan, Dedi; Mutiara, Indra; Martias, Martias; Ismail, Affero (Institute of Advanced Engineering and Science, 2025)
The objective of this study is to assess the effectiveness of the refrigeration technology training program at the vocational training centers (VTCs) by employing the context, input, process, product, and outcome evaluation approach. This study is classified as evaluative research, employing a qualitative description approach. Data collecting employs several approaches such as observation, interviews, and documentation. The primary informants in this study included the head of the VTC, the organizer of the VTC, the instructor of the refrigeration technology training, and the participants of the refrigeration technology training. Triangulation methods are employed to guarantee the accuracy and reliability of the data. The findings indicate that the setting, process, and product elements can be categorized as satisfactory, while the input and outcome aspects remain in the poor category. To increase employment and reduce unemployment, this split air conditioning training can be expanded by strengthening program components in the input aspect, particularly facilities, and infrastructure, as well as in the output aspect.